2018
DOI: 10.17161/jas.v4i1.6664
|View full text |Cite
|
Sign up to set email alerts
|

Concussion Knowledge of Youth Sport Athletes, Coaches, and Parents: A Review

Abstract: Mild traumatic brain injury, commonly known as a concussion, has gained widespread public attention. Approximately 1.1 to 1.9 million children ≤18 years old suffer sport/recreation-related concussions in the U.S. annually. The purpose of this review was to assess research articles examining concussion knowledge of youth sport athletes, coaches and parents. Twenty-one articles published from 2009-2016 were selected. The results of this review suggest that most athletes, coaches, and parents had good knowledge r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…Duff and Stuck 32 similarly surveyed SLPs about pediatric mTBI, and found that just 7% of respondents correctly rejected the statement that children show better recoveries than adults. Similar surveys of the public, including students, adults, and athletic coaches, show that this misconception is pervasive, 33 and that the majority of respondents misunderstand this principle tenant of recovery.…”
Section: Misconceptions In Foundational Knowledge: Understanding Consmentioning
confidence: 97%
“…Duff and Stuck 32 similarly surveyed SLPs about pediatric mTBI, and found that just 7% of respondents correctly rejected the statement that children show better recoveries than adults. Similar surveys of the public, including students, adults, and athletic coaches, show that this misconception is pervasive, 33 and that the majority of respondents misunderstand this principle tenant of recovery.…”
Section: Misconceptions In Foundational Knowledge: Understanding Consmentioning
confidence: 97%